Evaluation of children with severe neurological impairment admitted to hospital with pain and irritability - Isobel Fishman; Harold Siden; Christina Vadeboncoeur (BMC, 2022)
Abstract Background Pain is the most common symptom reported by caregivers of children with severe neurological impairment (SNI), a descriptive term for children with disorders affecting the neurological system across multiple domains. In SNI, cognition, communication, and motor skills are impaired and other organ systems are impacted. Pain is difficult to identify and treat in children with SNI because of communication impairment. When a clear cause of pain is not determined, the term "Pain and Irritability of Unknown Origin (PIUO)" is used to describe pain-like behaviours. This study explores the clinical care received by children with SNI admitted to hospital after presenting to the emergency department of a tertiary pediatric hospital with pain or irritability. Findings are compared to the approach suggested in the PIUO pathway, an integrated clinical pathway for identifying and treating underlying causes of pain and irritability in children with complex conditions and limited communication. Methods Retrospective chart review of children (age 0 to 18 years inclusive) with diagnoses compatible with SNI presenting with pain, irritability, and/or unexplained crying that required hospitalization between January 1st, 2019 and December 31st, 2019. Descriptive statistics were used to analyze the clinical care received by children in whom a source of pain was identified or not. In children for whom no cause of pain was identified, investigations completed were compared to the PIUO pathway. Results Eight hospital admissions of six unique children were included for data analysis. A cause for pain and irritability was identified and resolved in three patients. In children with PIUO, there were gaps in history taking, physical examination, and investigations that might have allowed a cause of pain and irritability to be found. Pain was assessed using the r-FLACC pain scale and varying medications for pain/irritability were given during each hospital admission. Conclusion Children with SNI admitted to a tertiary pediatric hospital did not undergo a standardized approach to identifying a cause of pain and irritability. Future efforts should explore the effectiveness of the PIUO pathway, a standardized approach to reducing and resolving pain in children with SNI.